3D DEM insights into the effect of particle overall regularity on macro and micro mechanical behaviours of dense sands. (April 2021) - Nie, Jia-Yan; Cao, Zi-Jun; Li, Dian-Qing; Cui, Yi-Fei
Abstract: Particle shape affects the mechanical properties of sands, but the underlying micro-mechanisms are not yet explored, at least partially, due to difficulties in accessing the particle scale information in the laboratory. This study aims to fill this gap through DEM by proposing a general framework for DEM simulation considering realistic particle shape and grading characteristics. Within the proposed framework, the irregular sand particle is approximated by 3D clump, and numerical triaxial drained compression tests are conducted for five granular assemblies of different overall regularity. The simulated critical state friction angles of these five assemblies are consistent with those predicted by an empirical formula proposed in the literature. The simulation results demonstrate that decreasing of overall regularity enhances the interlock effect between particles, making the assembly a higher stiffness and shear strength. Moreover, among different fabric anisotropies, the anisotropies of contact normal and normal contact force fabrics contribute to about 80% of the critical shear strength regardless of the overall regularity. With the decreasing of the overall regularity, the contribution of the anisotropy of contact normal fabric increases while that of normal contact force fabric decreases. The overall regularity mainly affects the anisotropies of contact normal and shear contact force fabrics.